PRODUCTION OF HYDROGEN USING FRESNEL LENS-SOLAR ELECTROCHEMICAL-CELL - ALKAN, C; SEKERCI, M; KUNC, S (Pergamon-Elsevier Science Ltd, 1995)
Concentrators such as concave mirrors, convex lenses and fresnel lenses have been used to reduce the cost of solar energy device systems. In this work a fresnel lens made of glass was tested to increase the efficiency of the solar cell. The fresnel lens used had a poor optical efficiency which vary around 0.7-0.8. Around 0.3% of solar energy was either reflected or absorbed by the lens. In our experiments the concentration ratio of the lens was found to be around four at optimum conditions. The efficiency of the solar cell varied up to 4% depending on solar energy values. The efficiency of the same cell under the fresnel lens was lowered by as much as five limes depending on solar energy. This efficiency value was found to be dependent on the positioning of the fresnel lens and solar cell with respect to the sunlight. The highest efficiency was obtained when both the cell and lens were placed perpendicular to sunlight. Hydrogen production was carried out with this solar energy conversion system as an electrical energy source. The overall efficiency of the system varied between 0.08-0.10%, depending on solar energy.